Flagella of Tumor-Targeting Bacteria Trigger Local Hemorrhage to Reprogram Tumor-Associated Macrophages for Improved Antitumor Therapy - Xu, Haiheng (Advanced materials (Deerfield Beach, Fla.), 2023)
© 2023 Wiley-VCH GmbH.